2004
DOI: 10.1075/is.5.1.05pep
|View full text |Cite
|
Sign up to set email alerts
|

Lack of referential vocal learning from LCD video by grey parrots (Psittacus erithacus)

Abstract: Grey parrots (Psittacus erithacus) do not acquire referential English labels when tutored with videotapes displayed on CRT screens if (a) socially isolated, (b) reward for attempted labels is possible, (c) trainers direct birds’ attention to the monitor, (d) live video feed avoids habituation or (d) one trainer repeats labels produced on video and rewards label attempts. Because birds learned referential labels from live tutor pairs in concurrent sessions, we concluded that video failed because input lacked li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Testing locations and living conditions when neither testing nor training was in progress were described in Pepperberg and Wilkes (2004). Food and water were available at his vocal request at all times during testing.…”
Section: Subjectmentioning
confidence: 99%
“…Testing locations and living conditions when neither testing nor training was in progress were described in Pepperberg and Wilkes (2004). Food and water were available at his vocal request at all times during testing.…”
Section: Subjectmentioning
confidence: 99%
“…Previous studies undertaken on heterospecific language acquisition showed that even if our birds had difficulties learning new words rapidly, they were able to use our labels for their own purpose such as food requests (Giret et al, 2009b). Moreover, several studies confirm the necessity of interactions with humans for referential learning (Pepperberg, 1994b;Pepperberg & McLaughlin, 1996;Pepperberg & Wilkes, 2004).…”
Section:  Discussionmentioning
confidence: 77%
“…Although Arthur had had about 3.5 years of intense human interaction, he had had the equivalent of only about a full year of communication training (i.e., he knew ''tickle'', ''hello'', a generic ''want some'', and two object labels; Pepperberg and Wilkes 2004). Housing is described in Pepperberg and Wilkes (2004).…”
Section: Subjectsmentioning
confidence: 99%